Influence of different cross-section on cyclic fatigue resistance of two nickel-titanium rotary instruments with same heat treatment: An in vitro study - Dario Di Nardo; Gianluca Gambarini; Marco Seracchiani; Alessandro Mazzoni; Alessio Zanza; Andrea Del Giudice; Maurilio D'Angelo; Luca Testarelli (Wolters Kluwer Medknow Publications, 2020)
Introduction: The aim of this study was to investigate the role of the cross-sectional design surface in improving the cyclic fatigue resistance by comparing two nickel-titanium (NiTi) rotary instruments with the same heat-treatment and grinding procedure. Materials and Methods: A total of 40 new NiTi instruments (20 S-One 25.06 taper and 20 AF Blue S4 25.06 taper) were tested in the present study. Both instruments were rotated at 300 rpm and with a torque setting of 2 Ncm) using an endodontic motor in the same artificial canal (90° angle of curvature and 3 mm radius). A Student's t-test was performed to determinate the differences in terms of time to fracture (TtF) and the length of the fractured portion between the two different instruments. Significance was set at P < 0.05. Results: The differences in terms of TtF for cyclic fatigue resistance between the two files were statistically significant (P < 0.05). In terms of fractured length, not statistically significant differences were found (P > 0.05). Scanning electron microscopy images showed patterns of cyclic fatigue striations. Conclusion: The results of this study confirm and enhance the role of cross-section in increasing the cyclic fatigue resistance of NiTi rotary instruments.